Α-Tocopherol Restriction Exacerbated Lipopolysaccharide-Induced Inflammatory Response in α-Tocopherol Transfer Protein-Null Mice. (14th June 2022) - Hashida, Megumi; Collins, Emily; Ranard, Katherine; Steelman, Andrew; Erdman, John
Abstract: Objectives: The α-tocopherol transfer protein-null ( Ttpa − / − ) mouse model is a valuable tool for studying the molecular and functional consequences of vitamin E (α-tocopherol, αT) deficiency. Our objective was to assess how dietary αT restriction, followed by lipopolysaccharide (LPS) exposure affected the inflammatory response in Ttpa − / − and wild-type ( Ttpa +/+ ) mice. Methods: After weaning (3 weeks of age), male Ttpa +/+ and Ttpa − / − littermates (n = 36/genotype) were fed an αT deficient diet ad libitum for 4 weeks. At 7 weeks of age, mice were injected with LPS (1 or 10 µg/mouse) or saline (control) intraperitoneally and sacrificed 4 hours post-injection. Brain and heart IL-6 levels, a marker of inflammatory response, and serum and tissue αT concentrations were measured via ELISA and HPLC-PDA, respectively. Hippocampal Il6, Tnf, and Gpx1 expression, markers of inflammatory and oxidative stress response, were measured via RT-qPCR, and blood immune cell profiles were measured via a hematology analyzer. Results: αT concentrations in serum and most analyzed tissues were below the limit of detection in Ttpa − / − mice but not Ttpa +/+ mice. Circulating white blood cell levels, particularly lymphocytes, were lower in all LPS groups compared to controls (P < 0.01). The 10 µg LPS groups had elevated IL-6 in the cerebellum and heart compared to controls, confirming an acute inflammatory response (P < 0.01). Hippocampal Il6 and Tnf expression were significantly increased in Ttpa − / − mice that received 10 µg LPS compared to those that received saline (∼20- and ∼3-fold higher, respectively) (P < 0.01). Comparing expression patterns by genotype, the 10 µg LPS- Ttpa − / − mice had ∼2-fold lower Gpx1 and ∼2-fold higher Il6 expression than the 10 µg LPS- Ttpa +/+ mice. Hippocampal Il6 expression was increased by LPS in a dose-dependent manner (P < 0.05). Conclusions: LPS, especially at the higher dose, altered inflammatory markers in the brain, heart, and serum. αT restriction further exacerbated the expression of select hippocampal genes. Funding Sources: Abbott Nutrition via the Center for Nutrition, Learning and Memory, University of Illinois, Urbana-Champaign; Division of Nutritional Sciences Vision 20/20 and Margin of Excellence Research grants.